Amerykańska percepcja twórczości Tadeusza Konwickiego - Sabo, Roman (Śląskie Studia Polonistyczne, 2020)
Due to dedicated efforts of the eminent American novelist Philip Roth, several novels from behind the Iron Curtain were published in the USA in the series “Writers from the Other Europe”. Starting in 1974, during the following 15 years, the novels of Andrzejewski, Borowski, Gombrowicz, Schulz and Konwicki were published by Penguin. This article concentrates on the American reception of Konwicki’s novels.